Famous Dinosaurs of Africa - Chinsamy-Turan, Anusuya; Chinsamy-Turan, Anusuya (Penguin Random House South Africa, 2013)
African dinosaurs make a significant contribution to palaeontology, but they are often omitted from books in favour of better-known species like T. Rex. But their fossils have been discovered across the continent ? from the Sahara Desert and the dusty plains of Kenya and Tanzania to the sandstone flats of the Karoo ? and they are no less magnificent or fascinating than their 'celebrity' cousins. Famous Dinosaurs of Africa is written for children, but has broad appeal for anyone interested in learning more about dinosaurs. A brief general introduction is followed by short chapters on dinosaur species, among them those that were fish-eating, sociable, predatory, etc, as well as those that were cannibals, and the biggest meat-eating dinosaur of all time ? the thread being that they all come from Africa. Details are given about where they were found, the meaning of their scientific names, and their size and diet. Spectacular, colourful illustrations bring the creatures vividly to life; photographs, maps and line drawings further illustrate the subject, while 'Unsolved' and 'Up close' panels add to the intrigue.